Financial Performance Analysis Using the Economic Value Added Method in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange - Febrianty, Febrianty; Syafitri, Ayu (International Journal of Multidisciplinary Sciences and Arts, 2022)
This study aims to determine the financial performance using the Economic Value Added (EVA) method in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the last five years (2016-2020 period). The research method used is a quantitative method with a descriptive approach. The data used is secondary data in the form of Company Financial Statements obtained from the official website of the Indonesia Stock Exchange. The results of the study were based on an analysis using the EVA method from five food and beverage companies that had good financial performance (positive EVA) during the 2016-2020 period, namely MLBI, MYOR, and ULTJ. Analysis of the company's performance with the method shows the EVA fluctuating results. This is because the value of NOPAT and capital charges is very influential on EVA results. Where if the NOPAT value is greater than the value of capital charges, the resulting EVA will increase and vice versa. The results of the EVA analysis show that positive accounting earnings do not always show the results that the EVA value is also positive. This is due to an increase in the cost of equity capital which greatly affects the value of WACC which results in an increase in the value of capital charges borne by the company, where the value of capital charges reduces the value of EVA.